2016
DOI: 10.1080/23809000.2016.1142357
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality-of-life questionnaires in head and neck cancer

Abstract: Questionnaires are an established means of quantifying health-related quality of life (HRQOL) following head and neck cancer. Questionnaires have evolved over many decades. Validated measures are now readily available to assess the physical/functional, emotional, and social impact of cancer and its treatment. The purpose of this article is to briefly reflect upon the current position and potential future improvements in questionnaire design and clinical utility. The basis for the observations stem from the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Furthermore, Veldhuis et al . asked participants to only recall their experiences during the previous week, which does not give a comprehensive reflection of their entire HEF experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Veldhuis et al . asked participants to only recall their experiences during the previous week, which does not give a comprehensive reflection of their entire HEF experience.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast to our findings, it has been reported in some of the previous quantitative literature that HEF has only a minimal impact on daily activities, hobbies and socialising (13,14,16) . Because the impact of HEF can vary day-to-day and week-to-week, restricting participants' responses to a single answer on a questionnaire can be difficult to interpret and of limited value (32) . Having set questions with predefined options may have meant that some aspects of the HEF experience were missed in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when trismus develops, prompt treatment should be given to prevent progression of the condition. Questionnaires such as the Mandibular Function Impairment Questionnaire and Helkimo Masticatory Dysfunction Index are often used for screening of temporomandibular disorders, including trismus . One study showed that for patients with no prior history of trismus, progression was insignificant during radiotherapy.…”
Section: Recommendationsmentioning
confidence: 99%
“…Questionnaires such as the Mandibular Function Impairment Questionnaire and Helkimo Masticatory Dysfunction Index are often used for screening of temporomandibular disorders, including trismus. 37 One study showed that for patients with no prior history of trismus, progression was insignificant during radiotherapy. However, following therapy, symptoms began within the first 9 months and then stabilized, with an average maximum incisal distance decrease of 32% 4 years after radiotherapy.…”
Section: Education Phasementioning
confidence: 99%